The amazing spectrum of light – LASER - Reddy, Lakshmi S; Guduri, Vineeth; P, Anoop Chowdary; Gosavi, Siddharth Y; Mohammed, Shammas (International Journal of Dental Materials, 2019)
“In right light at right time everything is extraordinary”- says Aaron Rose. This is very true with respect to lasers. Discovery of lasers from the spectrum of light has revolutionized the technology in many fields. The word “LASER” means Light Amplification by Stimulated Emission of Radiation. They offer many useful clinical applications for general dentists in the diagnosis and treatment of patients. There are many clinical, aesthetic, and psychological reasons to use lasers. Herein we present a brief overview of “THE AMAZING SPECTRUM OF LIGHT”